2012
DOI: 10.1002/hed.22976
|View full text |Cite
|
Sign up to set email alerts
|

Jugular and vagal paragangliomas: Systematic study of management with surgery and radiotherapy

Abstract: There is evidence that EBRT and SRS offer a similar chance of tumor control with lower risks of morbidity compared with surgery in patients with JPGs. Although the evidence is based on retrospective studies, these results suggest that surgery should be considered only for selected cases, but the decision should be individual for every patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
250
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 177 publications
(278 citation statements)
references
References 104 publications
(30 reference statements)
8
250
2
6
Order By: Relevance
“…In a large literature review on VPGLs and JTPGLs published in 2012, Suarez et al (2013a) described an average mortality rate of 1.3% with a GTR rate of 93.3%. However, the neurological risks are higher than those for CBTs: CN palsies are more common after surgery for JTPGLs and high-located VPGLs due to the tumoural involvement of the jugular foramen.…”
Section: Vagus Paragangliamentioning
confidence: 99%
See 1 more Smart Citation
“…In a large literature review on VPGLs and JTPGLs published in 2012, Suarez et al (2013a) described an average mortality rate of 1.3% with a GTR rate of 93.3%. However, the neurological risks are higher than those for CBTs: CN palsies are more common after surgery for JTPGLs and high-located VPGLs due to the tumoural involvement of the jugular foramen.…”
Section: Vagus Paragangliamentioning
confidence: 99%
“…An immediate postoperative CN palsy rate can be as high as 96 and 100% respectively for these tumours (Neskey et al 2011). The most affected component is the vagus nerve itself: in most series, a postoperative vagal deficit is almost universal (92-100%), by either paresis or necessary sacrifice during surgery (Urquhart et al 1994, Netterville et al 1998 (Suarez et al 2013a). The majority of patients need complex rehabilitation management regarding speech, swallowing and facial nerve deficits, but during follow-up, these deficits often recover partially (Netterville et al 1998).…”
Section: Vagus Paragangliamentioning
confidence: 99%
“…The results of surgery, EBRT, and SRS have been analyzed in a systematic review including 2042 patients with JPG or VPG [4]. Tumor control failure rate, major complication rate, and the number of cranial nerve palsies after treatment were significantly higher in surgical than in radiotherapytreated patients.…”
Section: Treatment Of Jugular and Vagal Paragangliomasmentioning
confidence: 99%
“…Similar studies on the trends of treatment are lacking in HNPG. Systematic analysis of the literature has shown that most of the HNPG have been treated surgically, with no data on the impact of observation in the management of these tumors [4,5]. …”
mentioning
confidence: 99%
See 1 more Smart Citation